Ksenofontova, Alexandra (2020), The Modernist Screenplay: Experimental Writing for Silent Film. Cham: Palgrave Macmillan imprint / Springer Nature Switzerland. - Nyström, Esbjörn (Moderna Språk, 2021)
--